Contemporary sample stacking in analytical electrophoresis. Issue 1 (9th October 2014) - Malá, Zdena; Šlampová, Andrea; Křivánková, Ludmila; Gebauer, Petr; Boček, Petr; El Rassi, Ziad
<x xml:space="preserve">Abstract</x> This contribution is a methodological review of the publications about the topic from the last 2 years. Therefore, it is primarily organized according to the methods and procedures used in surveyed papers and the origin and type of sample and specification of analytes form the secondary structure. The introductory part about navigation in the architecture of stacking brings a brief characterization of the various stacking methods, with the description of mutual links to each other and important differences among them. The main body of the article brings a survey of publications organized according to main principles of stacking and then according to the origin and type of the sample. Provided that the paper cited gave explicitly the relevant data, information about the BGE(s) used, procedure, detector employed, and reached LOD and/or concentration effect is given. The papers where the procedure used is a combination of diverse fragments and parts of various stacking techniques are mentioned in a special section on combined techniques. The concluding remarks in the final part of the review evaluate present state of art and the trends of sample stacking in CE.